The effect of gonadotropin-releasing hormone agonist downregulation in conjunction with hormone replacement therapy on endometrial preparation in patients for frozen–thawed embryo transfer - Hao, Haoying; Li, Meng; Zhang, Cuilian; Zhang, Shaodi (Frontiers in Medicine, 2024)
Objective: To investigate the effects of combining gonadotropin-releasing hormone agonist (GnRHa) downregulation with hormone replacement therapy (HRT, GnRHa-HRT) on the clinical outcomes of patients undergoing frozen-thawed embryo transfer (FET). Methods: In this retrospective study, we included patients who had FET between January 2018 and December 2022. They were categorized into HRT and GnRHa-HRT groups based on the endometrial preparation protocol. The study compared the clinical outcomes of patients in two groups. Possible factors affecting clinical outcomes were analyzed using univariate analysis. Multifactorial logistic regression was performed to analyze the impact of two endometrial preparation methods on clinical outcomes. Results: The rates of clinical pregnancy (47.31% vs. 59.60%), embryo implantation (37.58% vs. 49.65%), biochemical pregnancy (52.36% vs. 64.31%), and early abortion (7.07% vs. 10.77%) were statistically different between the two groups (P<0.05). Analysis using multifactorial logistic regression showed that there were 1.65-fold increasein clinical pregnancy rates (OR=1.65, 95% CI: 1.29-2.12, P<0.001) and 1.55-fold increase in embryo implantation rates (OR=1.55, 95% CI: 1.27-1.90, P<0.001) in the GnRHa-HRT group when compared to the HRT group. For blastocyst transfer, the GnRHa-HRT group's clinical pregnancy and implantation rates were significantly higher than those of the HRT group (OR=1.75, 95% CI: 1.30-2.37, P<0.001; OR=1.73, 95% CI: 1.35-2.21, P<0.001). Conclusions: In FET cycles, leuprorelin (as a GnRHa) downregulation combined with HRT may improve the clinical outcome of patients compared to the HRT cycle, especially for the clinical pregnancy and embryo implantation rates of patients with blastocyst transfer.